Theoretical Justification of Stresses Generated in the Working Equipment of the Hole Opener Weapon (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the article, resource-saving techniques and technologies for creating high-quality hole drainage in the subsoil layer of saline lands, as well as scientific methods of creating a new generation of modern preparations (liquids) that increase the porosity of the soil and ensure easy absorption of salts into the subsoil layer, and new generation of spraying techniques aimed at the development of the technical basis, the forces acting on the borehole openers, which served to wash the seepage waters under the saline soils, were analyzed.